Influence of dietary patterns and physical activity on bone mineral content and density, osteoporosis among children with stimulant use - Li, Qianqian; Zhou, Jiaxiu (Frontiers in Pediatrics, 2022)
Aim To examine the relationship between dietary patterns (DPs) and physical activity (PA) on bone mineral content (BMC), bone mineral density (BMD), and osteoporosis in children with stimulant use. Methods A cross-sectional study collected information on participants from the National Health and Nutrition Examination Survey (NHANES) via multistage stratified sampling. The baseline variables included the following: age, gender, the dietary approaches to stop hypertension (DASH) score, the Mediterranean diet (MD) score, and the Alternative Healthy Eating Index-2010 (AHEI-2010). The univariate and multivariate linear-regression analyses were carried out to explore the statistical correlation between the DPs and PA on BMC and BMD in children with stimulant use or non-stimulant use. In addition, we also investigated the association between DPs and PA on osteoporosis via logistic regression analyses. Results A total of 6,294 participants were eligibly enrolled in this study eventually. After adjusting age, gender, body mass index (BMI), race, family income, serum 25-hydroxyvitamin D, and serum cotinine, the multivariate linear-regression analysis showed that the MD was positively associated with total femur BMD, total femur BMC, femoral neck BMD, and femoral neck BMC among stimulant use group; high PA was associated with total femur BMD, total femur BMC, femoral neck BMD, femoral neck BMC, lumbar spine BMD, lumbar spine BMC and osteoporosis in stimulant use group. Conclusion Improved adherence to MD, DASH, AHEI-2010 or increased physical activity may increase BMD, BMC and reduce the risk of osteoporosis; children with stimulant use should improve their adherence to the MD and do more PA compared with children without stimulant use.